(untitled) - Elmas Nabilah Sani; Gianto Al Imron (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
This research revolves around the liability of pilgrims who use quotas from other countries, which causes the rights of other prospective pilgrims as consumers to be harmed. The purpose of this study is to determine the travel agency's liability to consumers towards the failure of their departure and to seek whether the Government of the Republic of Indonesia provides legal protection to pilgrims who use Hajj quotas from other countries. The researcher applied statute approach and conceptual approach to show that the liability of Hajj organizers is based on article 19 of the consumer protection law. In this case, the pilgrims of Indonesia who use the quota of another countries will not be provided by legal protection of the government. Both the consumers and the Hajj and Umrah Travel Bureau should be able to understand and respect their respective rights. The government also has a pivotal role in preventing violations of the law regarding Hajj.